Self-medication among medical student in King Abdul-Aziz University - Aashi, Mooataz Mohammed; Alghanmi, Hisham Abdulhamid; Alhibshi, Rabaa Hashim; Alsaati, Bashair Abdulrahim; Aljohani, Naif Jeza (International Journal of Research in Medical Sciences, 2016)
Background: A huge number of medications are used without prescriptions which make us face a real problem which is the overuse of medications. Medication overuse dose come with physical, mental and emotional abnormalities. The objective of the study was to investigate the irrational uses of these medications which are NSAIDS, paracetamol, antibiotic antihistamines, opioids, and anti-anxiety drugs among medical students in KAU. Methods: We conducted a descriptive cross sectional survey of 507 students enrolled at medical college of King Abdul-Aziz university in Jeddah 2015. The two steps stratified random sampling was used to collect the data. The questionnaire includes a socio-demographic information and data about using any of the following medication as anti-anxiety, antibiotics, paracetamol, opioids, (NSAIDs), and anti-histamine. The data entry and analysis was done by SPSS software package version 20. Results: Paracetamol were the most frequently 117 (23.1%) drug uses by medical students, followed by antihistaminic 48 (9.5%), antibiotic 33 (6.5%), NSAIDS 22 (4.3%), anti- anxiety 7 (1.4%) and opioid 4 (0.8%). Most of them were self-medication (74%). Relief fever was the most common cause for seeking self-medication reported by medical student 103 (20.4%), most frequent side effects was nausea and vomiting 47 (9.3%) Conclusions: There is an increase of self-medication in medical students of KAU especially paracetamol and NSAIDs use. We suggest increasing studies on the local irrational use of medications and increasing awareness on the importance of prescribed medications.